2017
DOI: 10.1634/theoncologist.2016-0419
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of PD-1/PD-L1 Inhibitors Compared with Chemotherapy in Patients with Advanced Cancer: A Meta-Analysis

Abstract: Background. Compared with chemotherapy, significant improvement in survival outcomes with the programmed death receptor-1 (PD-1) inhibitors nivolumab and pembrolizumab and the programmed death-ligand 1 (PD-L1) inhibitor atezolizumab has been shown in several types of advanced solid tumors. We conducted a systematic review and meta-analysis to compare safety and tolerability between PD-1/PD-L1 inhibitors and chemotherapy. Methods. PubMed and American Society of Clinical Oncology (ASCO) databases were searched 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
172
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(182 citation statements)
references
References 35 publications
3
172
2
5
Order By: Relevance
“…27 In this review, we investigated the quality of AE reporting as a surrogate of the reliability of AE rates reported in RCTs manuscripts. 27 In this review, we investigated the quality of AE reporting as a surrogate of the reliability of AE rates reported in RCTs manuscripts.…”
Section: Discussionmentioning
confidence: 99%
“…27 In this review, we investigated the quality of AE reporting as a surrogate of the reliability of AE rates reported in RCTs manuscripts. 27 In this review, we investigated the quality of AE reporting as a surrogate of the reliability of AE rates reported in RCTs manuscripts.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis of 3450 patients from 7 randomized controlled trials, treatment with ICIs was associated with a lower incidence of any‐grade AEs compared with chemotherapy (67.6% vs 82.9%) and grade 3 to 4 AEs (11.4% vs 35.7%), and treatment discontinuation occurred less frequently with anti–PD‐L1/PD‐1 agents compared with chemotherapy (4.5% vs 11.1%) 28. The incidence of TRAEs associated with ICIs ranged from 9% to 31%, with a pooled rate of 16% (95% confidence interval, 12%‐21%) 30.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that PD1/PD-L1 inhibitors are overall better tolerated than chemotherapy. [27] In lung cancer adenocarcinoma PD-L1 + cases convergence and cavitation were more frequently than did PD-L1 -cases. In contrast, surrounding ground glass opacities and air bronchogram were observed less frequently in PD-L1 + cases than in PD-L1 -cases.…”
Section: Pd-l1mentioning
confidence: 94%